2004
DOI: 10.1128/jcm.42.4.1396-1401.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Noroviruses Cocirculating in the North of England from 1998 to 2001

Abstract: A study was undertaken to investigate the diversity of noroviruses (NVs) in fecal samples from patients from 529 outbreaks and 141 sporadic cases of gastroenteritis in the North of England from September 1998 to August 2001. NV strains were detected by electron microscopy and characterized by a combination of the Grimsby virus antigen enzyme-linked immunosorbent assay, reverse transcriptase PCR, the heteroduplex mobility assay, and DNA sequencing. Twenty-one distinct NV strains, including several novel or vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 38 publications
7
41
1
Order By: Relevance
“…Since their first detection in The Netherlands in January 1995, the GGII.4 strains have consistently been present in the Dutch population (46). These observations are in agreement with those of other surveillance studies worldwide (3,4,15,17,29,36,55).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Since their first detection in The Netherlands in January 1995, the GGII.4 strains have consistently been present in the Dutch population (46). These observations are in agreement with those of other surveillance studies worldwide (3,4,15,17,29,36,55).…”
supporting
confidence: 83%
“…Since their first detection in The Netherlands in January 1995, the GGII.4 strains have consistently been present in the Dutch population (46). These observations are in agreement with those of other surveillance studies worldwide (3,4,15,17,29,36,55).During the past 15 years, four epidemic norovirus seasons have occurred, in the winters of 1995-1996, 2002-2003, 2004-2005, and 2006-2007. These worldwide epidemics were invariantly caused by the predominant genotype, GGII.4, and were attributed to the emergence of new variant lineages of this genotype (4,31,35,52,53).…”
supporting
confidence: 82%
“…Second, it has been suggested that the at Library on April 12, 2010 http://aje.oxfordjournals.org marked winter-time increase in hospital admissions for respiratory infections may drive the strong seasonality of norovirus outbreaks in this setting, and that there are distinct norovirus strains circulating in hospital populations and in the community that may have different transmission characteristics (29); therefore, the incidence of community disease or general practitioner consultations would not necessarily show the marked seasonality seen in health careassociated outbreaks. However, detailed characterization of the molecular epidemiology of norovirus infections in the community is needed, for comparison with the extensive data that already exist for hospital-acquired infections (30,31), to understand better the factors driving the different seasonality of health-care outbreaks and community disease. Finally, it is also possible that there was more outof-season norovirus transmission during this study because of the emergence of a new norovirus variant, as described above (32).…”
Section: Discussionmentioning
confidence: 99%
“…These viruses are frequently associated with diarrhea and vomiting in children under 5 years of age, and sporadic cases have been described for hospitalized children (9,10,22,25). NoV in particular are a major cause of outbreaks of gastroenteritis in adults in semiclosed institutions, including hospitals (11,24), nursing/retirement homes (11,17), cruise ships (13,30), and other settings (2,3,12).…”
mentioning
confidence: 99%